2013
DOI: 10.1074/jbc.m113.460287
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 Suppresses the Transactivation of Nuclear Factor of Activated T Cells by Targeting Multiple Genes and Inhibits the Proliferation of Pulmonary Artery Smooth Muscle Cells

Abstract: Background:The NFAT signaling pathway is linked to pulmonary arterial hypertension. Results: MicroRNA screening revealed that miR-124 robustly inhibits NFAT activity, dephosphorylation, and nuclear translocation of NFAT by targeting multiple genes, NFATc1, CAMTA1, and PTBP1. Conclusion: miR-124 is an effective and multipronged inhibitor of NFAT signaling. Significance: miR-124 might be a potential immunosuppressant that may have biological effects linked to pulmonary arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 62 publications
10
88
0
Order By: Relevance
“…The nuclear factor of activated T cells (NFAT) signaling pathway is linked to PASMC proliferation and PAH (55). Kang et al found that miR-124 inhibited NFAT receptor activity and decreased both the dephosphorylation and the nuclear translocation of NFAT (55). Hypoxia downregulated miR-124 in human PASMCs; consistent with the activation of NFAT during this process.…”
Section: Epigeneticsmentioning
confidence: 62%
See 1 more Smart Citation
“…The nuclear factor of activated T cells (NFAT) signaling pathway is linked to PASMC proliferation and PAH (55). Kang et al found that miR-124 inhibited NFAT receptor activity and decreased both the dephosphorylation and the nuclear translocation of NFAT (55). Hypoxia downregulated miR-124 in human PASMCs; consistent with the activation of NFAT during this process.…”
Section: Epigeneticsmentioning
confidence: 62%
“…Hypoxia downregulated miR-124 in human PASMCs; consistent with the activation of NFAT during this process. Overexpression of miR-124 not only inhibited human PASMC proliferation, but also maintained its differentiated phenotype by repressing the NFAT pathway (55). It was reported that miR-206 regulates PASMC proliferation and differentiation (56) and that miR-210 has antiapoptotic effects in PASMCs during hypoxia (57).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Kang et al observed that miRNA-124 exerted its antiproliferative and prodifferentiation effects in human PASMC by inhibiting NFATc1 dephosphorylation and nuclear translocation in chronic hypoxia-induced mouse PAH model. 38 By contrast, Chan et al demonstrated that activation of NFATc1 by phenamil may exhibit protective effects in hypoxia-induced SD rat PAH model. 47 The reason of the opposite effect of NFATc1 in PAH between 2 studies is unclear, but may be due to different animal models.…”
Section: Nfatc1 and Nfatc4mentioning
confidence: 99%
“…Therefore, the underlying molecular mechanisms by which NFAT proteins regulate the PASMC phenotype require further investigation. 38 NFATc3 may be involved in the entire hypoxic pulmonary vascular remodeling process, including initial proliferation and subsequent hypertrophy of PASMC. More evidence for NFATc3 involvement in PAH was provided by studies from other animal models.…”
Section: Nfatc3mentioning
confidence: 99%
“…Down-regulation of miR-124 in hypoxia-treated PASMC is consistent with the activation of NFAT signaling pathway in hypoxia by targeting NFATc1, CAMTA1 and PTBP1 genes [44]. Fhl-1 is a member of the LIM family and acts as an early key protein in the mechanism of PAH [45].…”
Section: Pahmentioning
confidence: 70%